Analisis Pengaruh Usaha Kerajinan Serabut Kelapa dengan Peningkatan Ekonomi Masyarakat Dusun Benyer Desa Telaga Waru Kecamatan Pringgabaya Kabupaten Lombok Timur - Agus Riswanto; Eliyani Nirwana (Universitas Hamzanwadi, 2017)
This study aims to determine whether there is a correlation between coconut fiber handicraft business with the improvement of the community's economy. This type of research uses quantitative research. The population in this research is all coconut fiber broom craftsman in Benyer Village Telaga Waru Village. While for the technique of sampling using technique probability sampling with simple random sampling. In collecting data using documentation technique, observation and questionnaire / questionnaire. Technique of data analysis by using validity test and reliability test, normality test, correlation analysis, coefficient of determination test and hypothesis test. Based on the technique of data analysis, based on validity and reliability test indicate that all item of question on variable X and variable Y is valid and reliable because the value of rvalue is bigger than rtable value (rvalue rtable). and on the normality test shows that all data is normally distributed. In the correlation test showed that the variable X (coconut fiber broom handling business) has a significant correlation with variable Y (economic improvement of society) because the value of rvalue is bigger than rtable value (0,244 0,207). And on the coefficient of determination test showed that as big as correlation between coconut fiber broom handicraft business with society economic improvement equal to 6% and the rest influenced by other factor not examined in this research. While on hypothesis test by using t test yield tvalue bigger than ttable value (2,331 1,6623) and significance value smaller than predetermined significant value that is 0,05 (0.02 0,05), hence can be stated that Ho is rejected and Ha accepted, meaning significant. So it can be concluded that the results of testing the hypothesis proved